Pengaruh Kenaikan Suku Bunga the Fed, Harga Minyak Dunia terhadap IHSG dalam Pergerakan Pasar Modal - Cindy Carolina Kurniasari; Yanna Eka Pratiwi; Siwidyah Desi Lasianti (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This study aims to determine the simultaneous and partial effects of The Fed Interest Rate, World Oil Prices, and World Gold Prices on the Composite Stock Price Index (CSPI), as well as identifying the dominant independent variable. The study's population includes The Fed Interest Rate, World Oil Prices, World Gold Prices, and the CSPI. The sample comprises all available data on The Fed Interest Rate, World Oil Prices, World Gold Prices, and the closing values of the CSPI at the end of each month from January 2019 to December 2022. The research employs a multiple linear regression analysis model processed using the SPSS 16 program. Hypothesis testing is conducted using statistical tests. The study's findings lead to several conclusions: (1) The Fed Interest Rate and World Oil Prices have a significant partial effect, whereas World Gold Prices do not significantly affect the CSPI on a partial basis. (2) Collectively, The Fed Interest Rate, World Oil Prices, and World Gold Prices significantly influence the CSPI. (3) Among the independent variables, The Fed Interest Rate emerges as the dominant factor affecting the CSPI.